Sztuka życia w wybranych poradnikach filozoficznych. Analiza porównawcza = The art of living in selected philosophical guides. Comparative analysis - Gajda, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper is a comparative study of selected philosophical guides published in Poland during the past decade. The main purpose is to characterize the similarities between them, such as recurring themes and references to the same philosophical figures and concepts. From this point of view, we could draw conclusions about the tendencies in guidebooks referring to philosophy, for example, the meaning of certain philosophers (mainly Stoics) and the dominant model of dealing with the everyday obstacles that they offer.
Keywords: sztuka życia; poradnik; filozofia praktyczna; stoicyzm; Śmierć; the art of living; self-help book; practical philosophy; stoicism; death